Correction: Mitochondria-targeted Ir@AuNRs as bifunctional therapeutic agents for hypoxia imaging and photothermal therapy. Issue 25 (18th March 2020) - Ke, Libing; Zhang, Cheng; Liao, Xinxing; Qiu, Kangqiang; Rees, Thomas W.; Chen, Yu; Zhao, Zizhuo; Ji, Liangnian; Chao, Hui
Abstract : Correction for 'Mitochondria-targeted Ir@AuNRs as bifunctional therapeutic agents for hypoxia imaging and photothermal therapy' by Libing Ke et al., Chem. Commun., 2019, 55, 10273–10276.